Supervisi Pendidikan: Langkah Strategis dalam Meningkatkan Mutu Pembelajaran - Murtyaningsih, Rina; Utami, Yeri (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study aims to analyze the role of educational supervision in enhancing learning quality through a qualitative approach with a descriptive design. Primary data were obtained through in-depth interviews with school principals, teachers, and educational supervisors, while secondary data were collected through document studies related to the implementation of supervision. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that educational supervision at MI Muhammadiyah Tambaksari, Blora Regency, plays a vital role in fostering teacher professionalism, enhancing learning effectiveness, and creating a culture of constructive evaluation. Structured and continuous supervision has proven effective in identifying challenges in learning, providing innovative solutions, and increasing collaboration between teachers and school administrators. However, the study also identified several obstacles, such as the heavy managerial workload of principals, insufficient preparation of teachers and principals, and inadequate facilities and infrastructure. To optimize the role of educational supervision, intensive training for supervisors, strengthened policy support, and improved communication between supervisors and teachers are required. This study concludes that educational supervision at MI Muhammadiyah Tambaksari, Blora Regency, is an effective instrument for driving improvements in learning quality.